Correlation Analysis Between Attentional Bias and Somatic Symptoms in Depressive Disorders - Wang, Yun; He, Yajun; Wang, Gaohua; Li, Jiangbo; Zhu, Haibing (Frontiers in Psychiatry, 2019)
Objective: To investigate the relationship between attentional bias and the severity of depression as assessed by the TORAWARE State and physical symptoms. Methods: We enrolled 55 patients with depression and 60 healthy. The Hamilton Depression Scale (HAMD-24), Somatic Self-rating Scale (SSS), and the Chinese Version of the Self-rating Scale for the TORAWARE State of Neurosis (SSTN) were selected to assess the severity of psychological symptoms. Dot-probe tasks were used to detect attentional bias. We then analyzed the correlation of attentional bias with the total scores on the symptom scales. Results: The negative attentional bias and negative disengaging index scores were both greater than 0 (t = 3.15 and 2.78, respectively; all P < 0.01). The negative attention bias score was positively correlated with the SSTN and negative disengaging index scores (r = 0.29 and 0.53, respectively; all P < 0.05). SSTN score was positively correlated with the total HAMD and SSS scores (r = 0.34 and 0.38, respectively; all P < 0.05). Conclusion: There is no direct correlation between negative attentionional bias and depression. It may be through the intermediate mechanism of TORAWARE State to influence symptoms.